An Integrative Habit of Mind : John Henry Newman on the Path to Wisdom - Aquino, Frederick D., 1963- (Book collections on Project MUSE., 2012)
Searching for better ways to inspire people to pursue wisdom, Frederick D. Aquino argues that teachers and researchers should focus less on state-of-the-art techniques and learning outcomes and instead pay more attention to the intellectual formation of their students. We should, Aquino contends, encourage the development of an integrative habit of mind, which entails cultivating the capacity to grasp how various pieces of data and areas of inquiry fit together and to understand how to apply this information to new situations.To fully explore this notion, An Integrative Habit of Mind brings the work of the great religious figure and educator John Henry Newman into fruitful conversation with recent philosophical developments in epistemology, cognition, and education. Aquino unearths some crucial but neglected themes from Newman's writings and carries them forward into the contemporary context, revealing how his ideas can help us broaden our horizons, render apt judgments, and better understand our world and how we think about it.